KONSEP PENDIDIKAN DALAM SASTRA BALI: DARI NANDURIN KARANG AWAK HINGGA JAYA PAṆḌITA RING AJI KABEH - I Gusti Made Swastya Dharma Pradnyan; I Wayan Juliana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Literature, life and education are a reciprocal theme. Literature as a reflection of life often presents a transmission in providing life guidance. Related to education, the essence of literature is to educate and provide entertainment. In Balinese literature, the concept of education or educating its readers is a didactic method that has been going on for a long time. Balinese literary writers include educational concepts so that their readers can be free from the darkness of the mind to enlightenment of the mind. Not a few Balinese literature emphasize the importance of learning, the goal is to produce an ability and skill that is useful in society. This study discusses the relationship between educational concepts spread in Balinese literature and categorizes them into one pattern. This study uses Julia Kristeva's intertextual theory which states that each text has a report in the previous text. By applying a qualitative approach, research data was collected using library study and recording techniques. The results of this study, first, display words related to the concept of education in Balinese literature. Second, interpret the concept of education in Balinese literature related to learning motivation.